Nilai Pendidikan Akhlak dalam Tradisi Kupatan Senen Pahing Anak Putu Trah Bonokeling di Desa Pekuncen Kecamatan Jatilawang Kabupaten Banyumas - Khoerotunnisa, Ana; Indianto, Dimas (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
The purpose of this study was to determine the process of implementing the Kupatan Senen Pahing tradition of the Bonokeling lineage children in Pekuncen Village, Jatilawang District, Banyumas Regency and to determine the values of moral education contained in the Kupatan Senen Pahing tradition. The researcher used a qualitative research type with an ethnographic approach. When analyzing the data, the researcher referred to James P. Spradley's theory. The theory describes 12 steps that researchers must take to reveal the formulation of the problems that have been prepared. The results of the study that the researcher obtained regarding the flow of the implementation of the Kupatan Senen Pahing tradition are that the Bonokeling lineage children gather at the Bedogol house, representatives of the Bonokeling lineage children perform the rikat pesarean of Kyai Bonokeling and friends, the Bonokeling lineage children gather at the Malang hall, the Bonokeling lineage children hold a deliberation, the Bonokeling lineage children perform mundu and continue with eating together. The moral education values contained in the Kupatan Senen Pahing tradition include the values of gratitude, tolerance, honoring guests, helping each other, justice, and preserving the environment.